Pharmacodynamic interaction between lumefantrine and desbutyl-benflumetol in Plasmodium falciparum in vitro - Alexander Leeb (2018)
The pharmacodynamic interaction between lumefantrine and monodesbutyl-benflumetol has been investigated in 44 fresh isolates of patients with a Plasmodium falciparum infection from the region of Mae Sot (Thailand). Both substances proved to be effective against parasite maturation within the test concentration range, with monodesbutyl-benflumetol being effective at a lower concentration than lumefantrine. Synergism between the two substances was evaluated with a combination of lumefantrine and monodesbutyl-benflumetol at a ratio of 4.25:1. The geometric mean values for complete inhibition of schizont maturation were 1035.7 nM for lumefantrine, 655 nM for monodesbutyl-benflumetol and 222.5 nM for the combination of both. An analysis for interaction according to the method of Berenbaum indicates a moderate synergism at the IC50, which gets stronger with increasing ICs and reaches the highest level at the IC99. The geometric mean of the sums of the FIC50is 0.73, of the FIC90it is 0.37 and of the FIC99it is 0.25. © 2010 Springer-Verlag.